2007
DOI: 10.1002/pmic.200600450
|View full text |Cite
|
Sign up to set email alerts
|

Identification of carbonylated proteins from enriched rat skeletal muscle mitochondria using affinity chromatography‐stable isotope labeling and tandem mass spectrometry

Abstract: We describe a strategy for the identification of carbonylated proteins from complex protein mixtures that combines biotin hydrazide labeling of protein carbonyl groups, avidin affinity chromatography, multiplexed iTRAQ reagent stable isotope labeling, and analysis using pulsed Q dissociation (PQD) operation on an LTQ linear ion trap mass spectrometer. This strategy provided the ability to distinguish biotin hydrazide labeled, avidin purified, carbonylated proteins from non-carbonylated background proteins with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 43 publications
2
124
0
Order By: Relevance
“…It should be noted that the optimal CE range for specific Q values and activation times does not seem to be a stable setting for all LTQ instruments. Different values have been published 28,32,33 and we and others 28 noticed that even on the same instrument optimal settings might fluctuate over time. However, as already mentioned, fragmentation efficiency is rather low in PQD, leading to low total ion currents in these experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the optimal CE range for specific Q values and activation times does not seem to be a stable setting for all LTQ instruments. Different values have been published 28,32,33 and we and others 28 noticed that even on the same instrument optimal settings might fluctuate over time. However, as already mentioned, fragmentation efficiency is rather low in PQD, leading to low total ion currents in these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…However, PQD suffers from very poor fragmentation efficiency and low product ion counts when compared to CID, 32,33 and is naturally less suited for precise quantitation. HCD fragmentation, on the other hand, offers high fragmentation efficiency, especially after introduction of an additional octopole dedicated for fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the production of ROS in skeletal muscle mitochondria, which increase with age and drive these protein modifications, mitochondrial muscle proteins are particularly susceptible to carbonylation (Meany et al, 2007). The age-associated fiber-type differences are observed in the susceptibility to of proteins to carbonylation.…”
Section: Carbonylation and Aging Skeletal Musclementioning
confidence: 99%
“…For example, one can use biotin hydrazine for the derivatisation of ketones and aldehydes, and avidin columns for specific isolation of derivatised peptides and proteins [93][94][95][96][97][98]. Interestingly, Mirzaei and Regnier [97] compared three different strategies based on biotin hydrazine tagging of carbonyls, affinity selection, proteolysis, RP-HPLC, and MS, and found that performing the affinity selection and chromatography at the protein level before proteolysis and mass spectrometric protein identification, was more informative because working with intact protein allowed the detection of crosslinked or truncated proteins.…”
Section: Carbonyl Enrichmentmentioning
confidence: 99%